Exploration of Diverse Secondary Metabolites From Streptomyces sp. YINM00001, Using Genome Mining and One Strain Many Compounds Approach - Liu, Tao; Ren, Zhen; Chunyu, Wei-Xun; Li, Gui-Ding; Chen, Xiu; Zhang, Zhou-Tian-Le; Sun, Hui-Bing; Wang, Mei; Xie, Tian-Peng; Wang, Meng; Chen, Jing-Yuan; Zhou, Hao; et al. (Frontiers in Microbiology, 2022)
A talented endophytic bacteria strain YINM00001, which showed strong antimicrobial activity and multiple antibiotic resistances, was isolated from a Chinese medicinal herb Peperomia dindygulensis Miq.. Phylogenetic analysis based on 16S rRNA gene sequences demonstrated that strain was closely related to Streptomyces anulatus NRRL B-2000T (99.93%). The complete genome of strain YINM00001 was sequenced. The RAxML phylogenomic tree also revealed that strain YINM00001 was steadily clustered on a branch with strain Streptomyces anulatus NRRL B-2000T under the 100 bootstrap values. The complete genome of strain YINM00001 consists of an 8,372,992 bp linear chromosome (71.72 mol% GC content) and a 317,781 bp circular plasmid (69.14 mol% GC content). Genome mining and OSMAC approach were carried out to investigate the biosynthetic potential of producing secondary metabolites. Fifty-two putative biosynthetic gene clusters of secondary metabolites were found, including the putative cycloheximide, dinactin, warkmycin, and anthracimycin biosynthetic gene clusters which consist with the strong antifungal and antibacterial activities exhibited by strain YINM00001. Two new compounds, peperodione (1) and peperophthalene (2), and 17 known compounds were isolated from different fermentation broth. Large amounts and high diversity of antimicrobial and/or anticancer compounds cycloheximide, dinactin, anthracimycin and their analogs had been found as predicted before, which highlights strain YINM00001 as an ideal candidate for further biosynthetic studies and production improvement of these valuable compounds. Meanwhile, several gene clusters that were highly conserved in several sequenced actinomycetes but significantly different from known gene clusters might be silent under proceeding fermentation conditions. Further studies, such as heterologous expression and genetic modification are needed to explore more novel compounds from this talented endophytic Streptomyces strain.